Factors Contributing to Hypertension Self-Care Management Behavior in Elderly Rural Residents - Silvanasari, Irwina Angelia; Basri, Achmad Ali; Maurida, Nurul; Vitaliati, Trisna (JURNAL INFO KESEHATAN, 2024)
The behavior of hypertension self-care management in the elderly is very important to be applied to reduce the prevalence of hypertension in rural areas. This study aims to analyze the factors associated with hypertension self-care management behavior in the elderly in rural areas based on the Protection Motivation Theory (PMT). The research design uses analytic observational with a cross-sectional approach. The sample in this study was 150 elderly people with hypertension who lived in rural areas. The independent variables are perceived vulnerability, perceived severity, perceived reward, response efficacy, self-efficacy, and intention. The dependent variable is hypertension self-care management behavior. Data collection uses the PMT and HSMBQ questionnaires. Bivariate analysis used the Spearman correlation test and multivariate analysis used linear regression with a significance level = 0.05. Bivariate test results found that perceived vulnerability (r=0.615 and p<0.05), perceived severity (r=0.497 and p<0.05), perceived reward (r=0.598 and p<0.05), efficacy response (r=0.510 and p<0.05), self-efficacy (r=0.477 and p<0.05), and intention (r=0.513 and p<0.05) related to hypertension self-care management behavior. Multivariate test results found that the PMT model associated with hypertension self-care management behavior includes perceived vulnerability (p<0.05), perceived severity (p<0.05), perceived reward (p<0.05), and self-efficacy (p<0.05). The value of R square = 0.519 indicates that the PMT model can predict 51.9% of self-care behavior. The dominant factor that can increase hypertension self-care management behavior is the perception of vulnerability. Nurses should be able to provide health education to improve hypertension self-care management behavior.